Induction in mice of human light-chain-associated amyloidosis. - Solomon, A. (1992)
Primary (idiopathic) or multiple myeloma-associated amyloidosis is characterized by the deposition in tissue of monoclonal light chains or light-chain fragments (AL amyloidosis). In contrast to other types of amyloidosis, information regarding the pathogenesis of light-chain-related amyloid has heretofore been limited due to the lack of a suitable in vivo model. The authors report the successful experimental induction of human AL amyloid deposits. The repeated injection into mice of Bence Jones proteins obtained from two patients with AL amyloidosis produced the histopathologic lesions characteristic of this disease. Partial dehydration of animals before protein injection resulted in the acceleration of amyloid formation. The human proteins were deposited as amyloid within the mouse renal blood vessel walls and parenchymal tissue, as well as in other organs. The deposits were Congo red-positive, exhibited green birefringence, and had a fibrillar ultrastructure. As evidenced immunohistochemically, the experimentally induced amyloid deposits consisted of the injected human light chains, and in addition, contained mouse amyloid P component (AP); mouse immunoglobulin (Ig) or inflammatory-associated amyloid A protein was not detected. Extraction and characterization of the amyloid deposits found within the mouse kidney revealed the presence of a predominantly intact human light polypeptide chain. Mice injected in identical manner with a non-amyloid-associated Bence Jones protein had no or only rare amyloid deposits. The experimental mouse model provides a means to ascertain the amyloidogenic potential of human monoclonal light chains and to study further the pathogenesis of AL amyloidosis.